Reciprocal and multi-species chromosome BAC painting in crucifers (Brassicaceae) - Lysak, M A; Mandáková, T; Lacombe, E (Cytogenetic and genome research, 2010)
In crucifer cytogenomics, BAC contigs of Arabidopsis thaliana have been used as probes for comparative chromosome painting among species. Here we successfully tested chromosome-specific BAC contigs of A. thaliana (n = 5) and A. halleri (n = 8) as probes for reciprocal BAC painting. Furthermore, BAC contigs of both Arabidopsis species were applied as multi-species painting probes to a third crucifer species, Noccaea caerulescens (n = 7), revealing their shared chromosome homeology. Specifically, we found homeology across portions of chromosomes At2, Ah4, and Nc4, which reflects their shared common origin with chromosome AK4 of the Ancestral Crucifer Karyotype (n = 8). We argue that multi-species and multi-directional painting will significantly expedite comparative cytogenomics in Brassicaceae and other plant families.
Keywords: Chromosome Painting; karyotypizace; Karyotyping; chromozomy rostlin; Species Specificity; umělé bakteriální chromozomy; Chromosomes, Artificial, Bacterial; Brassicaceae; Arabidopsis; In Situ Hybridization, Fluorescence; druhová specificita; Chromosomes, Plant; malování chromozomů; hybridizace in situ fluorescenční